2012
DOI: 10.1093/cercor/bhr288
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Damage in Frontotemporal Lobar Degeneration Spectrum

Abstract: White matter (WM) tract damage was assessed in patients with the behavioral variant frontotemporal dementia (bvFTD) and the 3 primary progressive aphasia (PPA) variants and compared with the corresponding brain atrophy patterns. Thirteen bvFTD and 20 PPA patients were studied. Tract-based spatial statistics and voxel-based morphometry were used. Patients with bvFTD showed widespread diffusion tensor magnetic resonance imaging (DT MRI) abnormalities affecting most of the WM bilaterally. In PPA patients, WM dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
142
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 45 publications
33
142
1
4
Order By: Relevance
“…The most important finding of the present study is that WM damage was more severe and more widely distributed than expected on the basis of cortical atrophy and the cognitive profiles, particularly in the atypical AD forms in which cortical atrophy remains localized and the clinical symptoms relatively focal. Together with the few previous studies in which WM damage was assessed in separate series of EOAD (4,18), PCA (22)(23)(24), and lvPPA (19)(20)(21), our findings indicate that DT MR imaging may be able to demonstrate subtle abnormalities along WM pathways that link atrophic regions with still unaffected gray matter regions. More importantly, we found that DT MR imaging has the potential to allow assessment of the extensive disorganization of brain networks in focal AD, even before overt cognitive deficits become apparent.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The most important finding of the present study is that WM damage was more severe and more widely distributed than expected on the basis of cortical atrophy and the cognitive profiles, particularly in the atypical AD forms in which cortical atrophy remains localized and the clinical symptoms relatively focal. Together with the few previous studies in which WM damage was assessed in separate series of EOAD (4,18), PCA (22)(23)(24), and lvPPA (19)(20)(21), our findings indicate that DT MR imaging may be able to demonstrate subtle abnormalities along WM pathways that link atrophic regions with still unaffected gray matter regions. More importantly, we found that DT MR imaging has the potential to allow assessment of the extensive disorganization of brain networks in focal AD, even before overt cognitive deficits become apparent.…”
Section: Discussionsupporting
confidence: 75%
“…Despite the growing number of studies that show that severe microstructural abnormalities occur NEURORADIOLOGY: White Matter Degeneration in Atypical Alzheimer Disease Caso et al along WM tracts in late-onset AD besides the known loss of neurons in the gray matter, to date, a few DT MR imaging studies have demonstrated the WM network involvement in EOAD (4,18), lvPPA (19)(20)(21), and PCA (22)(23)(24). To our knowledge, no study has been conducted to compare the patterns of WM damage in EOAD, lvPPA, and PCA.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…35,41,42,[44][45][46][47][48] DTI studies have provided consistent evidence for reduced structural connectivity in frontotem poral pathways in semantic PPA, and fronto-parietotemporal pathways in nonfluent PPA. [106][107][108] Evidence from task-free fMRI for the involvement of the language network in PPA variants is lacking, 44 but it is reasonable to predict that this network will be markedly affected in all PPA variants. Finally, the …”
Section: Alzheimer Disease Variantsmentioning
confidence: 99%
“…Cette technique permet de diffé rencier les APP logopé niques des deux autres variants d'APP et des troubles cognitifs lé gers amné siques due à une neuropathologie de maladies d'Alzheimer, non seulement au niveau du groupe, mais é galement au niveau individuel [77,78]. En effet, dans le cas des APP logopé niques, une atteinte bilaté rale pré dominant à gauche du faisceau unciné , des faisceaux longitudinaux supé rieur et infé rieur, des projections sous-corticales et du ré seau fronto-parié tal est observé e [77,[79][80][81]. Ces anomalies de la substance blanche sont é galement retrouvé es en dehors des zones atrophié es, permettant d'en faire un marqueur pré coce d'entré e dans la maladie [77,80].…”
Section: Irmunclassified
“…En effet, dans le cas des APP logopé niques, une atteinte bilaté rale pré dominant à gauche du faisceau unciné , des faisceaux longitudinaux supé rieur et infé rieur, des projections sous-corticales et du ré seau fronto-parié tal est observé e [77,[79][80][81]. Ces anomalies de la substance blanche sont é galement retrouvé es en dehors des zones atrophié es, permettant d'en faire un marqueur pré coce d'entré e dans la maladie [77,80].…”
Section: Irmunclassified